2016
DOI: 10.1038/nrm.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stem cell states: naive to primed pluripotency in rodents and humans

Abstract: The molecular mechanisms and signalling pathways that regulate the in vitro preservation of distinct pluripotent stem cell configurations, and their induction in somatic cells by direct reprogramming, constitute a highly exciting area of research. In this Review, we integrate recent discoveries related to isolating unique naive and primed pluripotent stem cell states with altered functional and molecular characteristics, and from different species. We provide an overview of the pathways underlying pluripotent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
449
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 515 publications
(463 citation statements)
references
References 121 publications
11
449
3
Order By: Relevance
“…This is possibly due to the different pluripotent states of hESC and mESCs, with mESCs being in a more naïve state (42). TBX3 overexpression cell culture models showed that it could promote hESC proliferation by repressing p14ARF and NFκBIB, an inhibitor of the NF-kappaB (NF-κB) pathway (41).…”
Section: Tbx3 In Development and In Stem Cell Biologymentioning
confidence: 99%
“…This is possibly due to the different pluripotent states of hESC and mESCs, with mESCs being in a more naïve state (42). TBX3 overexpression cell culture models showed that it could promote hESC proliferation by repressing p14ARF and NFκBIB, an inhibitor of the NF-kappaB (NF-κB) pathway (41).…”
Section: Tbx3 In Development and In Stem Cell Biologymentioning
confidence: 99%
“…For example, one critical variable impacting the functional pluripotency of conventional hPSCs is their developmental, molecular and epigenetic commonality with ʻprimed' mouse post-implantation epiblast stem cells (mEpiSCs) (Tesar et al, 2007;Brons et al, 2007;Chou et al, 2008;Kojima et al, 2014;Weinberger et al, 2016), which possess a less primitive pluripotency than inner cell mass (ICM)-derived mouse ESC (mESCs). For example, mEpiSCs cannot fully contribute to a blastocyst chimera and are resistant to chemical reversion to ICM-like naïve ʻground state' pluripotency with 'LIF-2i' (MEK/ERK and GSK3β signal inhibition) (Bernemann et al, 2011;Ying et al, 2008;Marks et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The robust spermatogonial stem cell culture in mice may reflect the more primitive developmental state of the mouse spermatogonial stem cells compared to the primate counterparts. In this context, it is tempting to speculate that the recently established concept of a naïve and a primed state of pluripotent stem cells [86] can also be translated to mouse (naïve) and primate (primed) spermatogonial stem cells.…”
Section: Spermatogonial Stem Cell Culturementioning
confidence: 99%